Impact of hepatic steatosis on treatment response of autoimmune hepatitis: A retrospective multicentre analysis - Liu, Peiyan; Li, Mingkai; Zhao, Lili; Yu, Hongsheng; Zhao, Chang; Chen, Jianning; Shi, Ruifang; Zhou, Li; Zhou, Qi; Wu, Bin; Li, Jia (Frontiers in Immunology, 2022)
Background There is a paucity of data on whether steatosis impacts autoimmune hepatitis (AIH) treatment response. We aimed to evaluate the influence of baseline steatosis on the biochemical response, fibrosis progression, and adverse longterm outcomes of AIH. Methods Steatosis was diagnosed by a controlled attenuation parameter (CAP) ≥ 248 dB / m. Only patients who underwent immunosuppressive therapy with available liver histological material at diagnosis and qualified CAP within seven days of the liver biopsy were included. Univariate and multivariate analyses were subsequently conducted. Results The multicentre and retrospective cohort enrolled 222 subjects (88.3% female, median age 54 years, median follow-up 48 months) in the final analysis, and 56 (25.2%) patients had hepatic steatosis. Diabetes, hypertension, and significant fibrosis at baseline were more common in the steatosis group than in the no steatosis group. After adjusting for confounding factors, hepatic steatosis was an independent predictor of insufficient biochemical response (OR: 8.07) and identified as an independent predictor of long-term adverse outcomes (HR: 4.07). By subgroup multivariate analysis (different degrees of steatosis, fibrosis, and prednisone dose), hepatic steatosis independently showed a relatively stable correlation with treatment response. Furthermore, in contrast to those without steatosis, a significant increase in liver stiffness (LS) was observed in patients with steatosis (4.1%/year vs. -16%/year, P < 0.001). Conclusions Concomitant hepatic steatosis was significantly associated with poor response to treatment in AIH patients. Routine CAP measurements are therefore essential to guide the management of AIH.